"Privatisation strategies and techniques / by R.K.Mishra,R.Nandagopal and Ch.Lakshmi Kumari" - "Mishra, R. K" (New Dehi, 2004)
The Performance of the State Level Public Enterprises (SLPEs) continues to remain a puzzle. They have been responsible for a substantial chunk of subsidies offered by the State governments. The second generation reforms aim to reduce the subsidies given by the states to their SLPEs in order to bring down their dependence on the Central Government, The present work makes an attempt to diddect the performance of the SLPEs in the various states and figure out the reasons responsible for their poor performance. An attempt has also been made to strategies the portfolio of these enterprises in the various states in terms of what shoud and what should not be retained by the various state governments.
Keywords: Privatisation